Demystifying murder: Open University pedagogy, social murder and the legacy of Steven Box - Drake, Deborah H. (Demystifying power, crime and social harm, 2023)
In 1983, Steven Box, published the influential book Power, Crime and Mystification, which considered the key question of why some harmful acts and behaviours are defined as illegal whilst others are not. Box points out that some criminalised harms—such as murder (e.g. intentional homicide)—are constructed in such a way that excludes other forms of avoidable death, notably those which are likely to be committed more often by those in power. Box, (1983: 8–9) argued that ‘[w]e are encouraged to see murder as a particular act involving a very limited range of stereotypical factors, instruments, situations and motives. Other types of avoidable killing are either defined as less serious crime than murder, or as matters more appropriate for administrative or civil interference’. This chapter extends this insight from Box by exploring the idea of ‘social murder’, a concept first introduced by Friedrich (Engels, 1845/2009). Drawing upon the example of the Grenfell Tower fire, we expand the idea of murder to include other avoidable deaths and, in so doing, shed light on the mystification of the concept of murder and the power of the state to both generate and prevent avoidable and premature deaths and how this has informed the pedagogy of The Open University, UK. We argue that if the problem of avoidable deaths is framed through the language of social murder, then solutions would look quite different than those offered by the criminal justice system and would be more focused on reversing the harms of inequalities. It would also mean taking a different approach to the way the harms in society are examined, thought about, and understood.